PENINGKATAN GROSS UP PADA SUMUR X DENGAN MELAKUKAN OPTIMASI ARTIFICIAL LIFT SRP KE ESP - Syaranamual, Estherlita Elizabeth (Petro : Jurnal Ilmiah Teknik Perminyakan, 2024)
Oil and gas are some of the components that are required in everyday life, from the needs of the community to the demands of industry, making oil and gas production a significant activity that requires attention. Producing oil in the field is deeply connected to a decrease in a reservoir pressure, which lowers the production rate, reduces the working fluid level to the pump setting, and lowers pump volumetric level, an artificial lift must be installed for the fluid to be produced. However, reservoir production may experience well problems such as water cuts, scaling, and others over time. If a well has a high water cut but has the characteristics of heavy oil, it is necessaryto increase the gross production of the well to optimize the oil recovery. An artificial lift SRP RWB CHIRCHILL C25-56-36 with a production rate 250 BFPD is installed in the X well. To increase the production rate, an ESP SST3021 artificial lift must be installed with a production rate of 3000 BFPD. As a result, an artificial lit optimization from SRP to ESP was performed to optimize the gross-up of well X.From several parameters, the author proves whether the optimization of artificial lift from SRP to ESP can increase oil and gas production. According to the hydrocarbon reserve specifications, well X still has 4032 MSTB of oil reserves, with a production duration of up to 2045 to achieve qlimit. Based on the simulation of nodal analysis, well X is simulated using an artificial lift ESP with a TGH4000 pump. The optimum flow rate obtained is 3999.08 MSTB, with the same number of stages and frequency values as the ESP installed in well X, which is 21 and the frequency value is 50 Hz. This proves that by optimizing ESP, the good flow rate increases.